Xenograft of Human Umbilical Mesenchymal Stem Cells from Wharton's Jelly Differentiating into Osteocytes and Reducing Osteoclast Activity Reverses Osteoporosis in Ovariectomized Rats. Issue 1 (January 2018) - Fu, Yu-Show; Lu, Chia-Hui; Chu, Kuo-An; Yeh, Chang-Ching; Chiang, Tung-Lin; Ko, Tsui-Ling; Chiu, Mei-Miao; Chen, Cheng-Fong
We examined the effects of human umbilical cord-derived mesenchymal stem cells (HUMSCs) in Wharton's jelly on ovariectomy (OVX)-induced osteoporosis by using in vitro and in vivo experiments. Two months after OVX, the rats gained weight and had a decreased serum estradiol level . Both micro-computed tomography (micro-CT) and histochemical analyses revealed a marked decrease in the bone volume (BV) and collagen content within the head, neck, and distal condyle of the femur, indicating that the osteoporosis animal model was successfully established 2 mo after bilateral OVX. Subsequently, 2.5 × 10 6 HUMSCs were injected into the bone marrow cavity of the left femurs 2 mo after OVX. The rats were divided into the following groups: normal + phosphate-buffered saline (PBS), normal + HUMSCs, OVX + PBS, and OVX + HUMSCs. Two months after transplantation, both micro-CT imaging and histochemical staining revealed that the normal + HUMSCs group had higher BV and collagen content in the epiphysis and metaphysis than did the normal + PBS group. In the OVX + HUMSCs group, a substantial increase in the rod-shaped trabecular bone and the abundant accumulation of collagen were observed around the site of HUMSC transplantation. Plenty of transplanted HUMSCs remained viable and differentiated into osteoblasts. In addition, HUMSC transplantation reduced the number of osteoclasts. Compared with HUMSCs cultured alone, HUMSCs cocultured with osteoblasts showed that the percentage of cells differentiating into osteoblasts significantly increased. Furthermore, osteoclasts cocultured with HUMSCs had significantly decreased cellular activity and differentiation capability. HUMSC transplantation into the distal femur of OVX rats could locally stimulate osteocalcin synthesis, increase the trabecular bone, and inhibit osteoclast activity.